Pharmacokinetics of Bocidelpar, ASP0367, in Renal and Hepatic Impairment: Results From Two Phase 1 Studies - Megumi Iwai; Nakyo Heo; Kentaro Hashimoto; Sayuri Guro; Selina Moy; Anna Spence; Tomasz Wojtkowski; Lauren Benner; Melanie Helmick; Tong Zhu; Brian C. Ferslew (Clinical and Translational Science)
ABSTRACT Bocidelpar is a peroxisome proliferator‐activated receptor δ modulator designed to address mitochondrial impairment. Two open‐label, single‐dose phase 1 studies (NCT05117294/NCT04942964) investigated the effect of severe renal or mild/moderate hepatic impairment on bocidelpar pharmacokinetics and safety. Adult participants received 75 mg bocidelpar and underwent serial blood and urine sampling over 4 days to evaluate the pharmacokinetics of bocidelpar. Thirteen participants were included in the renal cohort (severe impairment, n = 7; healthy participants, n = 6). A minimal increase was observed in the maximum concentration (Cmax) of the severe impairment group versus healthy participants (geometric least squares mean [GeoLSM] ratio [90% CI], 139.66% [86.33, 225.92]). No clear changes were observed in the area under the curve (AUC). Twenty‐five participants were included in the hepatic cohort (mild impairment, n = 8; moderate impairment, n = 8; healthy participants, n = 9). Compared with matched controls, increased Cmax was observed in the mild (GeoLSM ratio [90% CI], 181.37% [95.47, 344.56]) and moderate (GeoLSM ratio [90% CI], 298.78% [145.00, 615.65]) impairment groups. Mild impairment did not substantially affect the AUCinf versus matched controls (GeoLSM ratio [90% CI], 110.73% [82.16, 149.24]); however, it was higher in the moderate impairment group versus matched controls (GeoLSM ratio [90% CI], 195.58% [115.26, 331.88]). Across both studies, five treatment‐emergent adverse events were observed in five participants; all were considered mild in severity. Overall, bocidelpar was well tolerated and had an acceptable safety profile. Severe renal impairment had a minimal effect on bocidelpar pharmacokinetics, while moderate hepatic impairment resulted in increased bocidelpar concentration and exposure compared with matched controls.